Obesity Prevalence and Dietary Intake of Antioxidants in Native American Adolescents - Maria Cristina Perez; Benjamin D. Knisley; Grace E. Crosby; Shasha Zheng; M. Margaret Barth (Intelektual Pustaka Media Utama, 2016)
Antioxidants are well known for possessing anti-inflammatory properties, which can reduce the risk of chronic disease and obesity. However, very little research has been done to examine antioxidant intake among adolescent minority populations such as Native American adolescents. Our study examined the significance of antioxidant intake among Native American adolescents at an urban residential high school in Southern California. Our study population consisted of 183 male and female Native American adolescents, 14-18 years of age, representing 43 tribes from across the United States. Students’ primary source of meals was provided by the school food service. Based on the BMI calculations, the rate of obesity within our population was 38% for males and 40% for females, more than two-fold the national rate indicated by NHANESIII data. We used the Harvard School of Public Health Youth/Adolescent Questionnaire (HSPH YAQ), a semi-quantitative food frequency questionnaire, to examine antioxidant nutrient intake and evaluate the differences in the intake between normal and obese weight students. Statistical analysis of the results showed that intakes of vitamins C, E, and lycopene were the antioxidant nutrients found to be significantly different between normal and obese weight students and intakes of these nutrients were found to be higher among normal weight students (p-values = 0.02451, 0.00847, and 0.04928, respectively). These results suggest that dietary intake of antioxidants could be increased among Native American adolescents. Further research is needed to confirm our findings and identify effective ways for school food service to incorporate antioxidant rich foods into school menus.